Substrate specificity and promiscuity of horizontally transferred UDP-glycosyltransferases in the generalist herbivore Tetranychus urticae. (June 2019) - Snoeck, Simon; Pavlidi, Nena; Pipini, Dimitra; Vontas, John; Dermauw, Wannes; Van Leeuwen, Thomas
Abstract: Uridine diphosphate (UDP)-glycosyltransferases (UGTs) catalyze the addition of UDP-sugars to small hydrophobic molecules, turning them into more water-soluble metabolites. While their role in detoxification is well documented for vertebrates, arthropod UGTs have only recently been linked to the detoxification and sequestration of plant toxins and insecticides. The two-spotted spider mite Tetranychus urticae is a generalist herbivore notorious for rapidly developing resistance to insecticides and acaricides. We identified a set of eight UGT genes that were overexpressed in mites upon long-term acclimation or adaptation to a new host plant and/or in mite strains highly resistant to acaricides. Functional expression revealed that they were all catalytically active and that the majority preferred UDP-glucose as activated donor for glycosylation of model substrates. A high-throughput substrate screening of both plant secondary metabolites and pesticides revealed patterns of both substrate specificity and promiscuity. We further selected nine enzyme-substrate combinations for more comprehensive analysis and determined steady-state kinetic parameters. Among others, plant metabolites such as capsaicin and several flavonoids were shown to be glycosylated. The acaricide abamectin was also glycosylated by two UGTs and one of these was also overexpressed in an abamectin resistant strain. Our study corroborates the potential role of T. urticae UGTs in detoxification of both synthetic and natural xenobiotic compounds and paves the way for rapid substrate screening of arthropod UGTs. Graphical abstract: Image 1 Highlights: 8 UDP-glycosyltransferases (UGTs) from T. urticae were functionally expressed in E. coli and shown to be catalytically active. Most recombinant T. urticae UGTs preferred UDP-glucose as the activated sugar donor. A high-throughput screening was performed with 44 substrates comprising both plant secondary metabolites and acaricides. Kinetic parameters for nine enzyme-acceptor combinations as well as their preferred UDP-donor substrate were determined.